Regulatory perspectives on medical device approval in global jurisdictions. (September 2013) - Kaushik, Deepak; Rai, Shivaji; Dureja, Harish; Mittal, Vineet; Khatkar, Anurag
Today medical device sector is evolving to find the new horizons. Medical device approval is a time-consuming process that requires submission of safety, efficacy and quality documentation to national regulatory bodies in various countries. While there are some similarities among the countries regarding medical device regulations, some differences also exist that significantly affect the regulatory scrutiny. This presents a great problem for manufacturers marketing their products in multiple countries. Competent authorities worldwide have begun to realize the problem and collaborate to harmonize the regulations. In the present article regulatory approval procedure is discussed in different jurisdictions such as United States, European Union, Japan, China and India along with comparisons in terms of classification of devices, competent authorities, rules and regulations and quality management systems involved in these countries.